2013
DOI: 10.3109/01676830.2013.764452
|View full text |Cite
|
Sign up to set email alerts
|

Enucleation versus Evisceration in Ocular Trauma: A Retrospective Review and Study of Current Literature

Abstract: Surgical decision-making in ocular trauma is largely based on surgeon preference and experience, with minimal evidence in the literature to support either enucleation or evisceration. We recommend evisceration over enucleation in cases of reliable patient follow-up due to the low incidence of sympathetic ophthalmia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 13 publications
2
40
0
2
Order By: Relevance
“…Such higher incidence among men is previously reported from several other geographical regions. [678910111213]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such higher incidence among men is previously reported from several other geographical regions. [678910111213]…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 83.4% of the surgeries were enucleation, 13.4% were evisceration, and 3.2% were exantration, which is consistent with the previous reports. [357] Contradicting this, other studies have reported evisceration as the major surgical approach. [89]…”
Section: Discussionmentioning
confidence: 99%
“…According to the 2001–2010 report by the Trauma Center, at University Hospital, Newark, New Jersey, 6.0% of 183 work-related injured eyes underwent enucleation, 45 and 45.9% of 148 assault-related injured eyes with NLP and 31.1% received enucleation 46 . According to the 2001–2012 report of the Trauma Center in Queens, New York, there were 441 cases of eye injuries, with the enucleation rate of 5.0% 47 . By comparing with the high rate in the Trauma Center, University Hospital, we can find that China has made remarkable achievement in the education and medical treatment for eye injuries in recent years.…”
Section: Comprehensive Development Of Medical Treatment For Eye Injurmentioning
confidence: 99%
“…[6][7][8] Three ocular-orbital-palpebral surgeries are related to ocular bulb removal: evisceration, comprising the partial removal of the ocular bulb with conservation of the sclera; enucleation, comprising the total removal of the bulb with only the capsule and oculomotor muscles remaining; and exenteration, comprising the removal of all contents of the orbital cavity and the circumjacent tissue. [9][10][11][12][13][14] To rehabilitate patients with deformities of the ocular bulb, an ocular prosthesis may be used. [15][16][17][18][19][20] Prosthesis use improves the patient's aesthetic appearance, helping their psychosocial development and improving their quality of life.…”
mentioning
confidence: 99%
“…related to the presence of other muscles in the upper part, such as the levator palpebrae superioris, which is normally preserved in the anophthalmic cavity after enucleation of the ocular bulb, [9][10][11][12][13] aiding the movement of the future prosthesis.…”
mentioning
confidence: 99%